Assessment of the reliability of a custom built Nordic Ski Ergometer for cross-country skiing power test - Bortolan, L.; Pellegrini, B.; Finizia, G.; Schena, F. (The Journal of Sports Medicine and Physical Fitness, 2008)
Aim: Despite the recent development of cross-country ski technique having led to an increase in the importance of upper body power, there is a substantial lack of specific equipment for upper body force and power evaluation. In order to achieve good reproducibility of the skiing motion, a new upper body ergometer has been developed in our lab and tested by elite cross-country skiers. In this study, the reliability of this device was assessed comparing upper body power measurements with double poling ski performance in the field. Methods: The new apparatus consists of an electric motor acting as load and actively controlled by a personal computer on the basis of force and velocity data. Nine cross-country skiers (age: 21.7±3.12 years; body weight: 72.2±3.8 kg), competing at international level, performed a ski test on a 1.2 km long sprint track and a 50 s exercise on the Nordic Ski Ergometer. The velocity of the last section (180 m, slope 1.37%) of the track, performed using the double poling technique at maximal voluntary intensity, was related to the upper body power measured at the ergometer. Results: Mean upper body power was 9.22±2.29 W·kg-1, while average velocity on the section considered was 6.66±0.67 m·s-1. A high correlation (R2=0.871) was found between upper body power and ski velocity. Conclusion: In addition to overcoming the main limitations that affect traditionally used equipment, the strong relationship between the parameters obtained with the new ergometer and ski velocity indicates their ability to assess athletes performance. The new apparatus could therefore be considered a ski specific testing equipment for cross-country skiers which is useful for reproducing upper body involvement in cross-country ski-ing in a laboratory setting.